(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Over the past decades, the consumption of energy drinks has increased significantly worldwide, particularly among adolescents and university students. These beverages are commonly used during periods of intense mental and emotional stress, such as exam preparation, late-night studying, or prolonged intellectual work. According to various studies, a considerable proportion of students regularly consume energy drinks in order to improve alertness, enhance concentration, and reduce feelings of fatigue.